Intergenerational conflict between young and old on public education spending: a revisit / Wong Sing Yun, Rudy Ansar and Faerozh Madli - Wong, Sing Yun; Ansar, Rudy; Madli, Faerozh (Faculty of Business and Management, 2022)
The intergenerational conflict over public education allocation has remained to be a subject of contentious debate. As such, this study aimed to examine the impact of the elderly population and young population growth that could potentially affect educational spending within the context of Malaysia. This study will employ the Autoregressive Distributed Lag (ARDL) method to determine the intergenerational conflict on public education expenditure in Malaysia. The empirical finding from this study demonstrated the significant influence of both the elderly and young population on public education spending. Any increase in the young population was followed by a proportional increase in education expenditure. Meanwhile, the increase in the elderly population does not appear to reduce public education spending. This implied that there is intergenerational conflict which would put pressure on public education spending. The changes in population structure could bring implications as to how the public expenditure will be allocated. The evidence from this paper will further provide useful insight and policy recommendations to policymakers on how to improve education financing in the future.